Evaluation of a new intraoral paralleling device for creating guiding planes: A pilot study - Borges, Alexandre Luiz Souto [UNESP]; Borges, Alessandra Bühler [UNESP]; Uemura, Eduardo Shigueyuki [UNESP]; Paes-Júnior, Tarcisio José de Arruda [UNESP]; Tango, Rubens Nisie [UNESP]; de Araújo, José Eduardo Junho [UNESP]; Kimpara, Estevão Tomomitsu [UNESP] (My University, 2010)
Aim: The aim of the study was to assess the accuracy of a new intraoral paralleling device for creating proximal guiding planes for removable partial dental prostheses. Methods and Materials: Thirty gypsum casts were divided into two groups in which the proximal surfaces of selected teeth were prepared using either a surveying device (Group 1) or the new ParalAB paralleling device (Group 2). In each cast guiding planes were prepared on the distal surface of the maxillary left canine (A), on the mesial and distal surfaces of the maxillary left second molar (B and C), and on the distal surface of the maxillary right canine (D). Each prepared surface formed an angle related to the occlusal plane that was measured five times and averaged by one operator using a tridimensional coordinate machine. Results: The mean guiding plane angles (± standard deviation) for the prepared surfaces were A=91.82° (±0.48°, B=90.47° (±0.47°, C=90.21° (±0.76°, and D=90.50° (±0.73°) for the dental surveyor (Group 1) and A=92.18° (±0.87°), B=90.90° (±0.85°), C=90.07° (±0.92°), and D=90.66° (±0.76°) for the ParalAB paralleling device (Group 2). A two-way ANOVA, Tukey's, and Levène's tests (at p<0.05) revealed statistically significant differences among surfaces prepared by both groups and that one surface Conclusions: The ParalAB device was able to prepare parallel surfaces and despite significant difference between groups, the ParalAB presented a small deviation from absolute parallelism and can be considered a valid method to transfer guide plans in the fabrication of removable partial dentures. Clinical Significance: The preparation of suitable guiding planes on abutment teeth during the fabrication of removable partial dentures is dependent on the ability of the operator and requires considerable chair time. When multiple teeth are involved, achieving parallelism between abutment surfaces can be technically challenging, especially in posterior regions of the mouth. The ParalAB prototype intraoral paralleling device can aid the clinician during the preparation of accurate guiding planes with a minimum degree of occlusal divergence. © 2010 Seer Publishing LLC.
Keywords: Guide plane; Intraoral surveyor; Path of insertion; Removable partial denture